2021
DOI: 10.3390/app12010344
|View full text |Cite
|
Sign up to set email alerts
|

IMU: A Content Replacement Policy for CCN, Based on Immature Content Selection

Abstract: In-network caching is the essential part of Content-Centric Networking (CCN). The main aim of a CCN caching module is data distribution within the network. Each CCN node can cache content according to its placement policy. Therefore, it is fully equipped to meet the requirements of future networks demands. The placement strategy decides to cache the content at the optimized location and minimize content redundancy within the network. When cache capacity is full, the content eviction policy decides which conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Figure 5 shows the result of the aforementioned simulation, which is similar to the result achieved earlier and presented in Figures 2b and 3 The results presented in this section are particularly inconsistent with those achieved in [5], where the network performance in terms of CHR increases when the number of CS increases up to about 40% and then decreases with the number of CS above this threshold. However, the results are consistent with ones achieved in [6], where the CHR increases with the continuous increasing in the number of CS, or in [7][8][9][10][11][12][13][14][15][16]50] which evaluate the network performance with a constant number of CS but different sizes.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…Figure 5 shows the result of the aforementioned simulation, which is similar to the result achieved earlier and presented in Figures 2b and 3 The results presented in this section are particularly inconsistent with those achieved in [5], where the network performance in terms of CHR increases when the number of CS increases up to about 40% and then decreases with the number of CS above this threshold. However, the results are consistent with ones achieved in [6], where the CHR increases with the continuous increasing in the number of CS, or in [7][8][9][10][11][12][13][14][15][16]50] which evaluate the network performance with a constant number of CS but different sizes.…”
supporting
confidence: 83%
“…The authors concluded that the proposed solution presents better performance than others in terms of the chosen metrics. The immature used (IMU) replacement policy was proposed in [15]. Besides the popularity, the proposal resorts to the content maturity index, which is calculated by using the content arrival time and its frequency within a specific time frame.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…However, balancing between content popularity and cache gain can complicate eviction decisions, such as when a higher cache gain increases the perceived value of less popular content. Rashid et al (2021) proposed another cache replacement policy for content-centric networks named Immature Used (IMU). This policy aims to address the issue of holding onto currently unpopular content and prematurely evicting potentially popular content.…”
Section: Dynamic Popularitymentioning
confidence: 99%